Analysis of fiber deposition using automatic image processing method - Bělka, Miloslav; Lízal, František; Jedelský, Jan; Jícha, Miroslav (EDP Sciences, 2013)
Fibers are permanent threat for a human health. They have an ability to penetrate deeper in the human lung, deposit there and cause health hazards, e.g. lung cancer. An experiment was carried out to gain more data about deposition of fibers. Monodisperse glass fibers were delivered into a realistic model of human airways with an inspiratory flow rate of 30 l/min. Replica included human airways from oral cavity up to seventh generation of branching. Deposited fibers were rinsed from the model and placed on nitrocellulose filters after the delivery. A new novel method was established for deposition data acquisition. The method is based on a principle of image analysis. The images were captured by high definition camera attached to a phase contrast microscope. Results of new method were compared with standard PCM method, which follows methodology NIOSH 7400, and a good match was found. The new method was found applicable for evaluation of fibers and deposition fraction and deposition efficiency were calculated afterwards.

Fibers are permanent threat for a human health. They have an ability to penetrate deeper in the human lung, deposit there and cause health hazards, e.g. lung cancer. An experiment was carried out to gain more data about deposition of fibers. Monodisperse glass fibers were delivered into a realistic model of human airways with an inspiratory flow rate of 30 l/min. Replica included human airways from oral cavity up to seventh generation of branching. Deposited fibers were rinsed from the model and placed on nitrocellulose filters after the delivery. A new novel method was established for deposition data acquisition. The method is based on a principle of image analysis. The images were captured by high definition camera attached to a phase contrast microscope. Results of new method were compared with standard PCM method, which follows methodology NIOSH 7400, and a good match was found. The new method was found applicable for evaluation of fibers and deposition fraction and deposition efficiency were calculated afterwards.
Analysis of fiber deposition using automatic image processing method
Keywords: aerosol; deposition; human lungs; fibers; deposition fraction and efficiency; image analysis; phase-contrast microscopy; aerosol; deposition; human lungs; fibers; deposition fraction and efficiency; image analysis; phase-contrast microscopy